Development of quantitative metrics of plume migration at geologic CO2 storage sites. Issue 4 (16th July 2019) - Harp, Dylan; Onishi, Tsubasa; Chu, Shaoping; Chen, Bailian; Pawar, Rajesh
Abstract: We develop plume migration metrics based on spatial moment analysis methods that quantify the spatio‐temporal evolution of plumes at geologic CO2 storage sites. The metrics are generalized to handle any 3‐D scalar attribute field values. Within the geologic CO2 storage context, these can be parameters such as CO2 saturation, effective pressure, overpressure, dissolved CO2 concentration, total dissolved solids, pH, and other attributes that are critical for assessing risks. The metrics are comprehensive in that they can effectively handle and account for complex continuous and discontinuous plumes and intra‐plume migration. We demonstrate the metrics on simulated CO2 plumes injected into flat and tilted reservoirs with homogeneous and heterogeneous permeability fields. Using these idealized reservoir scenarios, we demonstrate the information that the metrics extract, showing that the metrics elucidate nuances in plume migration not apparent by standard approaches to the scalar fields values. Published 2019. This article is a U.S. Government work and is in the public domain in the USA.